A Development of Dental Service System in Type-2 Diabetic Patients at Kongra Hospital, Phatthalung Province - Wareerat, Chakraphong; Hintao, Janpim; Pithpornchaiyakul, Wattana (Area Based Development Research Journal, 2019)
The aim of this action research is to develop a dental service system for type-2 diabetic patients at Kongra Hospital, Phatthalung province. The research is carried out from 1 October 2017 to 30 April 2018. The development of the dental service system is divided into 4 phases: 1) the problem survey phase, 2) the design phase, 3) the implementation phase, and 4) the evaluation phase. The samples are selected based on a set of selection criteria. The research features 15 type-2 diabetes mellitus patients, 11 members of the multidisciplinary team and 2 stakeholders. The qualitative data are collected using in-depth interview technique and transcription data using word by word for content analysis. The quantitative data are collected using periodontal status form and data are analyzed using descriptive statistics. The results of the research in the view of the sample show rises in both prevalence and severity of type-2 diabetes mellitus in Kongra district, Phatthalung province. The existing dental service system at Kongra Hospital is found to be difficult to access by type-2 diabetes patients and reactive in nature. The development of the dental service system relies on cooperation between diabetic patients and service providers to design and constantly launch activities that suit the context, meet the key of type-2 diabetic patients seeking dental treatments, and fit the capacity of the service unit. The dental services developed under this research include the creation of special channels for dental treatment and the improvement of individualized diabetes booklets and telephone notification. It has proved to increase the rate of dental service utilization and improve periodontal status of type-2 diabetic patients.